Accommodation and Compromise in the Contact Zone: Christianity and Chinese Culture in Modern Hong Kong Literature - Yang, Yi (Religions, 2024)
Situated in the unique historical context of Hong Kong—a contact zone between East and West—this study explores how Christianity’s introduction through British colonialism and missionary efforts has intertwined with and influenced Chinese cultural traditions. By examining selected works of Xu Dishan and Chen Zanyi, this study reveals the dynamic negotiations of identity and values between these two cultural and religious traditions. These literary works not only depict the complexities of cultural hybridity but also provide insights into the evolving nature of cultural identity in Hong Kong, illustrating how global religions and local traditions can merge and transform each other. This study contributes to understanding the intricate dance of religious exchange, conflict, and compromise in Hong Kong’s cross-culture setting, suggesting that such literary explorations can bridge Christianity with the socio-economic, cultural, and historical fabric of Chinese society.